Exploring the mTOR Signalling Pathway and Its Inhibitory Scope in Cancer - Suhail Ahmad Mir; Ashraf Dar; Saad Ali Alshehri; Shadma Wahab; Laraibah Hamid; Mohammad Ali Abdullah Almoyad; Tabasum Ali; Ghulam Nabi Bader (Pharmaceuticals, 2023)
Mechanistic target of rapamycin (mTOR) is a protein kinase that regulates cellular growth, development, survival, and metabolism through integration of diverse extracellular and intracellular stimuli. Additionally, mTOR is involved in interplay of signalling pathways that regulate apoptosis and autophagy. In cells, mTOR is assembled into two complexes, mTORC1 and mTORC2. While mTORC1 is regulated by energy consumption, protein intake, mechanical stimuli, and growth factors, mTORC2 is regulated by insulin-like growth factor-1 receptor (IGF-1R), and epidermal growth factor receptor (EGFR). mTOR signalling pathways are considered the hallmark in cancer due to their dysregulation in approximately 70% of cancers. Through downstream regulators, ribosomal protein S6 kinase β-1 (S6K1) and eukaryotic translation initiation factor 4E binding protein 1 (4E-BP1), mTORC1 influences various anabolic and catabolic processes in the cell. In recent years, several mTOR inhibitors have been developed with the aim of treating different cancers. In this review, we will explore the current developments in the mTOR signalling pathway and its importance for being targeted by various inhibitors in anti-cancer therapeutics.